2022
DOI: 10.31557/apjcp.2022.23.12.3971
|View full text |Cite
|
Sign up to set email alerts
|

Cultural, Religious and Socio-Ethical Misconceptions among Muslim Women towards Breast Cancer Screening: A Systematic Review

Abstract: Introduction: Breast cancer is the most diagnosed cancer worldwide. With an estimated 685,000 deaths, female breast cancer was the fifth leading cause of cancer mortality worldwide, accounting for 6.9% of all cancer deaths. Previous studies have shown that late detection and delayed diagnosis are associated with advanced-stage breast cancer and poor survival. Factors contributing to non-adherence to breast cancer screening among women were elicited from previous studies. However, few studies have focused on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(197 reference statements)
0
2
0
Order By: Relevance
“…Palestinian cancer patients may struggle with infertility, changing social roles, body image, sexual issues, and strained relationships ( 29 , 30 ). Many studies have found that Arab women may hide breast cancer from friends, family, and neighbors due to social stigma ( 29 , 30 ). Moreover, Arab women perceive cancer as a punishment or a divine test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palestinian cancer patients may struggle with infertility, changing social roles, body image, sexual issues, and strained relationships ( 29 , 30 ). Many studies have found that Arab women may hide breast cancer from friends, family, and neighbors due to social stigma ( 29 , 30 ). Moreover, Arab women perceive cancer as a punishment or a divine test.…”
Section: Introductionmentioning
confidence: 99%
“…The concerns center on the stigma associated with breast examination, the potential reaction of the spouse upon discovering a lump, and the impact of cultural and religious modesty ( 30 ). This may exacerbate their psychological distress and anxiety about mortality, influencing breast cancer detection and prognosis ( 29 , 30 ). According to Madkhali et al ( 31 ), Arab women with breast cancer frequently seek medical attention only at the advanced stage of the disease, with large breast lumps that are difficult to manage at home and cause intense pain.…”
Section: Introductionmentioning
confidence: 99%
“…Religious beliefs in relation to healthcare and cancer screening are complex but some studies indicated that higher levels of religiosity have been associated with delays in seeking healthcare (Azhar et al, 2022; Vu et al, 2016). Negative religious coping, viewing health problems as a punishment from God (Padela et al, 2015), and fatalistic beliefs have been reported in the literature (Moey et al, 2022). Structural factors include cost (Islam et al, 2017) and perceived discrimination (Azhar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent systematic review on cultural, religious and socio-ethical misconceptions among Muslim women towards BC screening (Moey et al, 2022) indicated that Muslim women with high levels of religiosity tend to perceive disease less seriously as they believe what occurred in their lives is attributable to Allah (s.w.t. ), their protector (Kawar, 2013;Hajian et al, 2017;Zorogastua et al, 2017;Shaw et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review was conducted on related studies that have been published globally over the past ten years. The search strategy was performed through four databases namely, PubMed, Cochrane Library, Scopus and Science Direct (Moey et al, 2022).…”
Section: Introductionmentioning
confidence: 99%